The orchid flora of Cocos Island National Park, Puntarenas, Costa Rica - Bogarín Chaves, Diego Gerardo (2011)
The orchid flora of Cocos Island National Park, Costa Rica is described based on field collections and herbarium sampling. Cocos Island is an oceanic island situated 550 km south-west of Puntarenas (the main Costa Rican port on the Pacific coast) and 680 km north-east of the Galápagos Islands. Five species of orchids were recorded in this small area of 24 km2: Camaridium micranthum and Ornithidium adendrobium (both formerly included in Maxillaria) and three endemic species of Epidendrum (E. cocoense, E. insulanum and E. jimenezii). The species are described and analytical illustrations are provided for each. A key to the species for field identification based on morphology is presented. Biogeography, ecology, taxonomy, evolution and conservation status of the species are also discussed.